SENSITIVITAS ETIS MAHASISWA JURUSAN AKUNTANSI POLITEKNIK NEGERI MEDAN - Asriyati Asriyati (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
The integration of ethics into accounting curriculum becomes a critical challenge faced by educators in the field of accounting. The importance of ethical education in accounting has been recognized by both practitioners and academics. This study will describe whether there is a difference in ethical sensitivity between male and female students. Using the Independent Samples T-Test analysis will be compared on average of the two groups that are not related to each other, to find out whether the two averages have the same or no significant value. The sample for this research is some accounting students of State Polytechnic of Medan. The amount of sample in this study is sufficient according to the sample determined by 100 respondents in proportion of 50 male students and 50 female students. Sampling method in this research is non probability method with purposive sampling with criterion of final accounting student with reason of final level student have got ethics charged course. The results showed that there were significant differences in ethical sensitivity between male accounting students and female accounting students. The level of ethical sensitivity in female accounting students is better than the ethical sensitivity of male accounting students. There are significant differences in ethical sensitivity between the accounting students of the first semester and the accounting students of the final semester. The degree of ethical sensitivity in accounting students of the final semester is better than the ethical sensitivity of accounting students in the early semester.